Proceedings of the Conference on Photon Interaction in the V-energy Range - Conference on Photon Interaction in the V-Energy Range, (January 26-30, 1963 : Cambridge, Massachusetts); Feld, Bernard Taub, 1919- (Cambridge. Mass.: M I T Press, 1965)
40